Supramolecular polymerization of sulfated dendritic peptide amphiphiles into multivalent L-selectin binders - Straßburger, David; Herziger, Svenja; Huth, Katharina; Urschbach, Moritz; Haag, Rainer; Besenius, Pol (Beilstein Journal of Organic Chemistry, 2021)
The synthesis of a sulfate-modified dendritic peptide amphiphile and its self-assembly into one-dimensional rod-like architectures in aqueous medium is reported. The influence of the ionic strength on the supramolecular polymerization was probed via circular dichroism spectroscopy and cryogenic transmission electron microscopy. Physiological salt concentrations efficiently screen the charges of the dendritic building block equipped with eight sulfate groups and trigger the formation of rigid supramolecular polymers. Since multivalent sulfated supramolecular structures mimic naturally occurring L-selectin ligands, the corresponding affinity was evaluated using a competitive SPR binding assay and benchmarked to an ethylene glycol-decorated supramolecular polymer.
Keywords: L-selectin binders; multivalency; self-assembly in water; supramolecular polymers

(untitled) - Mammen, M.; Choi, S.-K.; Whitesides, G. M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Mulder, A.; Huskens, J.; Reinhoudt, D. N. (Org. Biomol. Chem., 2004)

(untitled) - Mammen, M.; Dahmann, G.; Whitesides, G. M. (J. Med. Chem., 1995)

(untitled) - Lees, W. J.; Spaltenstein, A.; Kingery-Wood, J. E.; Whitesides, G. M. (J. Med. Chem., 1994)

(untitled) - Mochalova, L. V.; Tuzikov, A. B.; Marinina, V. P.; Gambaryan, A. S.; Byramova, N. E.; Bovin, N. V.; Matrosovich, M. N. (Antiviral Res., 1994)

(untitled) - Lee, R. T.; Lin, P.; Lee, Y. C. (Biochemistry, 1984)

(untitled) - DeFrees, S. A.; Kosch, W.; Way, W.; Paulson, J. C.; Sabesan, S.; Halcomb, R. L.; Huang, D.-H.; Ichikawa, Y.; Wong, C.-H. (J. Am. Chem. Soc., 1995)

(untitled) - Gestwicki, J. E.; Strong, L. E.; Kiessling, L. L. (Chem. Biol., 2000)

(untitled) - Bertozzi, C. R.; Kiessling, L. L. (Science, 2001)

(untitled) - Röglin, L.; Lempens, E. H. M.; Meijer, E. W. (Angew. Chem., Int. Ed., 2011)

(untitled) - Choi, S.-K.; Mammen, M.; Whitesides, G. M. (J. Am. Chem. Soc., 1997)

(untitled) - Sigal, G. B.; Mammen, M.; Dahmann, G.; Whitesides, G. M. (J. Am. Chem. Soc., 1996)

(untitled) - Kiessling, L. L.; Strong, L. E.; Gestwicki, J. E. (Annu. Rep. Med. Chem., 2000)

(untitled) - Wu, K.; Liu, J.; Johnson, R. N.; Yang, J.; Kopeček, J. (Angew. Chem., Int. Ed., 2010)

(untitled) - Martos, V.; Castreño, P.; Valero, J.; de Mendoza, J. (Curr. Opin. Chem. Biol., 2008)

(untitled) - Krieg, E.; Bastings, M. M. C.; Besenius, P.; Rybtchinski, B. (Chem. Rev., 2016)

(untitled) - Hartgerink, J. D.; Beniash, E.; Stupp, S. I. (Science, 2001)

(untitled) - Frisch, H.; Unsleber, J. P.; Lüdeker, D.; Peterlechner, M.; Brunklaus, G.; Waller, M.; Besenius, P. (Angew. Chem., Int. Ed., 2013)

(untitled) - Lasky, L. A. (Annu. Rev. Biochem., 1995)

(untitled) - McEver, R.; Moore, K.; Cummings, R. (J. Biol. Chem., 1995)

(untitled) - Coussens, L. M.; Werb, Z. (Nature, 2002)

(untitled) - Simanek, E. E.; McGarvey, G. J.; Jablonowski, J. A.; Wong, C.-H. (Chem. Rev., 1998)

(untitled) - Somers, W. S.; Tang, J.; Shaw, G. D.; Camphausen, R. T. (Cell, 2000)

(untitled) - Norgard-Sumnicht, K. E.; Varki, N. M.; Varki, A. (Science, 1993)

(untitled) - Dernedde, J.; Rausch, A.; Weinhart, M.; Enders, S.; Tauber, R.; Licha, K.; Schirner, M.; Zügel, U.; von Bonin, A.; Haag, R. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Weinhart, M.; Gröger, D.; Enders, S.; Riese, S. B.; Dernedde, J.; Kainthan, R. K.; Brooks, D. E.; Haag, R. (Macromol. Biosci., 2011)

(untitled) - Paulus, F.; Schulze, R.; Steinhilber, D.; Zieringer, M.; Steinke, I.; Welker, P.; Licha, K.; Wedepohl, S.; Dernedde, J.; Haag, R. (Macromol. Biosci., 2014)

(untitled) - Kumari, S.; Achazi, K.; Dey, P.; Haag, R.; Dernedde, J. (Biomacromolecules, 2019)

(untitled) - Ehrmann, S.; Chu, C.-W.; Kumari, S.; Silberreis, K.; Böttcher, C.; Dernedde, J.; Ravoo, B. J.; Haag, R. (J. Mater. Chem. B, 2018)

(untitled) - Straßburger, D.; Stergiou, N.; Urschbach, M.; Yurugi, H.; Spitzer, D.; Schollmeyer, D.; Schmitt, E.; Besenius, P. (ChemBioChem, 2018)

(untitled) - Lee, S. S.; Fyrner, T.; Chen, F.; Álvarez, Z.; Sleep, E.; Chun, D. S.; Weiner, J. A.; Cook, R. W.; Freshman, R. D.; Schallmo, M. S.; Katchko, K. M.; Schneider, A. D.; et al. (Nat. Nanotechnol., 2017)

(untitled) - Hendrikse, S. I. S.; Spaans, S.; Meijer, E. W.; Dankers, P. Y. W. (Biomacromolecules, 2018)

(untitled) - Newkome, G. R.; Shreiner, C. (Chem. Rev., 2010)

(untitled) - Berac, C. M.; Zengerling, L.; Straβburger, D.; Otter, R.; Urschbach, M.; Besenius, P. (Macromol. Rapid Commun., 2020)

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)

(untitled) - Tornøe, C. W.; Christensen, C.; Meldal, M. (J. Org. Chem., 2002)

(untitled) - Wilson, A. J.; van Gestel, J.; Sijbesma, R. P.; Meijer, E. W. (Chem. Commun., 2006)

(untitled) - Engel, M.; Burris, C. W.; Slate, C. A.; Erickson, B. W. (Tetrahedron, 1993)

(untitled) - Appel, R.; Fuchs, J.; Tyrrell, S. M.; Korevaar, P. A.; Stuart, M. C. A.; Voets, I. K.; Schönhoff, M.; Besenius, P. (Chem. – Eur. J., 2015)

(untitled) - von Gröning, M.; de Feijter, I.; Stuart, M. C. A.; Voets, I. K.; Besenius, P. (J. Mater. Chem. B, 2013)

(untitled) - Appel, R.; Tacke, S.; Klingauf, J.; Besenius, P. (Org. Biomol. Chem., 2015)

(untitled) - Frisch, H.; Nie, Y.; Raunser, S.; Besenius, P. (Chem. – Eur. J., 2015)

(untitled) - Ohi, M.; Li, Y.; Cheng, Y.; Walz, T. (Biol. Proced. Online, 2004)